Influence of Organizational Adaptability and Technology Use on the Competence of Sungai Penuh City Health Service Employees Through Training Satisfaction as an Intervening Variable - Linda Sumarni; Heryanto (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the influence of organizational adaptability and technology use on employee competency at the Sungai Penuh City Health Office, both directly and indirectly, through training satisfaction as an intervening variable. This study employed a quantitative approach with a survey method. The population was all Sungai Penuh City Health Office employees, with a sample size of 50 respondents determined using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis, classical assumption tests, hypothesis testing (t-test and F-test), the coefficient of determination, and the Sobel test to examine the mediating role. The results showed that organizational adaptability and technology use had a positive and significant effect on training satisfaction. Furthermore, training satisfaction, organizational adaptability, and technology use also had a positive and significant effect on employee competency. The Sobel test results demonstrated that training satisfaction acted as a partial mediator in the influence of organizational adaptability and technology use on employee competency. This study concluded that improving employee competency at the Sungai Penuh City Health Office can be achieved through strengthening organizational adaptability, optimizing technology use, and providing high-quality training that provides employee satisfaction.